PENGEMBANGAN SUMBER DAYA MANUSIA DI DINAS KOMUNIKASI INFORMATIKA PERSANDIAN DAN STATISTIK PROVINSI SULAWESI UTARA - Hesi Virdiawati Lumasuge; Shirley Y.V.I. Goni; Grace J. Waleleng (Sam Ratulangi University, 2021)
The purpose of this research was to find out about the development of human resources in the Office of Communication, Informatics, Encoding and Statistics of North Sulawesi Province. This research used a qualitative approach that aims to dig up information. The type of data used are primary and secondary data collected by observation, interview and documentation techniques. The results of this study indicate that the aspects of training and learning at the Communication, Informatics, Encoding and Statistics Office of North Sulawesi are going well where the state civil apparatus has conducted learning independently or personally and has participated in many trainings organized by the government or related agencies. Furthermore, the education aspect is still considered not going well because there is no financial assistance such as scholarships as a form of educational assistance given to employees who want to continue their studies or education to a higher level.